2004
DOI: 10.1136/jnnp.2002.000414
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes at 18 months after good neurological recovery from aneurysmal subarachnoid haemorrhage

Abstract: Objectives: To evaluate functioning, 18 months after surgery, of 49 patients with good neurological recovery following aneurysmal subarachnoid haemorrhage (SAH), and to determine the extent of any improvements in disturbances of mood, cognitive functioning, and levels of activity and participation previously observed at 9 month follow up. Methods: SAH patients, matched for age, gender, and occupation with healthy control participants, completely quantitative measures of mood (HADS, FIES, BDI) and activity/part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
3
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 26 publications
4
121
3
6
Order By: Relevance
“…In addition, after 3 months, 60% of patients, and after 9 months, 30% of patients showed a high ratio of PTSD. Reviewing the study conducted 18 months after surgery by the identical investigators on the identical patients, PTSD symptoms were decreased slightly, but on the other hand, in the anxiety scale of the Hospital Anxiety and Depression Scale (HADS), the clinical range was increased from 17 to 18.4%, the HADS depression scale was increased from 8.5 to 10.2%, and anxiety or depression became slightly higher than after 9 months from the time of their operation 27) . According to this study, despite the absence of cognitive defect or physiological disability, 50% of patients were dependent on others to carry out routine life, and they did not participate in productive activities including any volunteer activity, paid working activity, babysitting, education, etc.…”
Section: )mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, after 3 months, 60% of patients, and after 9 months, 30% of patients showed a high ratio of PTSD. Reviewing the study conducted 18 months after surgery by the identical investigators on the identical patients, PTSD symptoms were decreased slightly, but on the other hand, in the anxiety scale of the Hospital Anxiety and Depression Scale (HADS), the clinical range was increased from 17 to 18.4%, the HADS depression scale was increased from 8.5 to 10.2%, and anxiety or depression became slightly higher than after 9 months from the time of their operation 27) . According to this study, despite the absence of cognitive defect or physiological disability, 50% of patients were dependent on others to carry out routine life, and they did not participate in productive activities including any volunteer activity, paid working activity, babysitting, education, etc.…”
Section: )mentioning
confidence: 97%
“…However, the assessment of the prognosis of SAH by such grades is only limited to the evaluation of the recovery of the neurological function of patients. Generally, the survival rate of SAH patients has been increased and the physical symptoms of patient have also been lessened, nevertheless, numerous studies have shown that the patients still experience depression and anxiety 1,2,7,11,24,26,27) . Therefore, although most patients recover physiologically after their treatments, they may experience deterioration in the quality of life (QOL) due to psychological problems such as anxiety, depression as well as the difficulty to return to their everyday social activities.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with unfavorable cognitive outcome include initial disease severity, the amount of subarachnoid blood, aneurysm location, and the occurrence of secondary complications such as delayed cerebral ischemia, and elevated intracranial pressure 2, 3. Cognitive and psychosocial long‐term deficits were also reported in SAH patients with “good clinical grade,” uneventful clinical course, and no evidence of structural brain damage 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…16,23,[28][29][30][31]34,35 Several authors provided evidence supporting the hypothesis that psychosocial impairment after SAH is heavily influenced by the psychological trauma. 1,3,15,16,[27][28][29][30]34,37 However, we cannot exclude the possibility that these marked emotional problems may stem, at least in part, from premorbid psychological stress. 1,30,33,37 Lindberg et al 22 speculated that inadequate coping is the major obstacle in the return to active life, particularly after an illness with a sudden onset.…”
Section: Psychological Traumatization and Quality Of Lifementioning
confidence: 91%
“…6,15,16,23,25,28,29,31,34,35,38 These psychological changes and subjective complaints are also present even when the degree of neurological and/or cognitive impairment is relatively mild. 15,16,23,25,[28][29][30][31]35,38 Ropper and Zervas 35 and Ljunggren et al 23 found that approximately 25% of their SAH patients with a good neurological result (Glasgow Outcome Scale [GOS] score of 1) exhibited substantial emotional maladjustment.…”
mentioning
confidence: 99%